2018
DOI: 10.3199/iscb.13.9
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hybridization without homoeologous chromosome paring in the <i>Dryopteris varia</i> complex (Dryopteridaceae)

Abstract: ABSTRACT:Controlling combining chromosomes in meiosis is necessary to maintain genome constitutions. The Dryopteirs varia complex is one of the apogamous fern groups which perform recurrent hybridization with unequal meiosis, and produce spores after meiosis of the genome doubling in spore mother cells. We analyzed five low-copy nuclear markers (AK1, EST, GapCp, G6PD, and PgiC) and three regions of plastid DNA (rbL, ndhF and trnL-F). The genetic constitution of the five nuclear markers was the same in the D. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Hybridization is considered to be common in ferns (Barrington et al., ; Sigel, ); however, surprisingly, no accurate estimation of hybridization rates in natural populations has been published for ferns. Many studies have described fern hybrid taxa, including intergeneric ones (e.g., Brownsey, ; Reichstein, ; Knobloch et al., ; Rothfels et al., ), or studied the presence of hybrids in natural fern populations (Zhang et al., ; Testo et al., ; Ekrt and Koutecký, ; Hori et al., ; Hanušová et al., ). However, hybridization rates have only been described qualitatively in these studies, without any precise evaluation.…”
mentioning
confidence: 99%
“…Hybridization is considered to be common in ferns (Barrington et al., ; Sigel, ); however, surprisingly, no accurate estimation of hybridization rates in natural populations has been published for ferns. Many studies have described fern hybrid taxa, including intergeneric ones (e.g., Brownsey, ; Reichstein, ; Knobloch et al., ; Rothfels et al., ), or studied the presence of hybrids in natural fern populations (Zhang et al., ; Testo et al., ; Ekrt and Koutecký, ; Hori et al., ; Hanušová et al., ). However, hybridization rates have only been described qualitatively in these studies, without any precise evaluation.…”
mentioning
confidence: 99%
“…We counted chromosomes from living plants of D. dickinsii and D. tsutsuiana collected and their localities were in Appendix 1. The methods are followed by Hori et al (2018). To estimate the reproductive mode of each sample or herbarium specimen, the spores in each sporangium were counted.…”
Section: Methodsmentioning
confidence: 99%
“…For molecular analyses, total DNA was extracted from the silica-dried leaves by using cetyltrimethylammonium bromide solution, according to the method of Doyle and Doyle (1990). ndhF was used as the maternal inherited cpDNA marker (Kuo et al 2016, Hori et al 2018, Table 1. Taxa (cytotypes reported in the previous study with references and newly reported in this study with asterisks), voucher, cytotype in this study and allele constitution of the Dryopteris atrata complex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations